Performance Analysis of Polarization Diversity for Indoor Scenarios at 41.4 GHz and 61.5 GHz - Ana Vazquez Alejos; Manuel Garcia Sanchez; Iñigo Cuiñas (International Journal of Antennas and Propagation)
We present the radio channel experiments conducted in indoor scenarios to test the performance of a dual orthogonal polarization scheme in the single-branch receiver end of a mobile system with a centre frequency of 41.4 GHz and 61.5 GHz. The diversity gain has been obtained according to three main combination methods for an outage probability of 1%: signal selection, equal gain combining, and maximal ratio combining. Diversity gain calculated ranges from 0.25 to 4.5 dB, depending on the combination technique used, the radiation pattern, the scenario, and the frequency band. The spatial variation of the cross-polar discrimination factor (XPD) has been estimated. The XPD ranges from 31 dB to 34 dB at 41.4 GHz and between 26 dB and 29 dB for the 61.5 GHz band. From the gain and discrimination results, we evaluated the performance of this scheme to conclude its suitability as either a diversity technique for reducing signal fading, as the 41.4 GHz, or as a method for increasing the link capacity in the 61.5 GHz case.